Single-file reciprocating system for curved canals preparation: a case report - Asrianti Asrianti; Nurhayaty Natsir (DiscoverSys Inc., 2018)
Objective: Preparation of curved canal is the ultimate challenge in endodontic treatment. Various incidents could occur during preparation such as ledges, perforations, and zip. Modification instruments have been made to avoid those incidents, can be used according to the canal shape. Reportedly, rotary reciprocating instrument can be used for curved canals because it can maintain canal shape, with or without little alignment. This case report discusses the use of a single file reciprocating system for the preparation of curved canal in the second molar left mandible.Methods: A 22-years-old male patient came to Dental Hospital Hasanuddin University complained about decay of his molar left mandible and felt pain while eating. Radiographic image appears normal at 37 with curved canals in mesial roots and straight canal in distal root along with thickening of periodontal ligament space. Endodontic treatment was performed with preparation of curved canals using rotary WaveOne GOLD file in mesial root and Protaper Universal in distal root. Restoration was done with metal onlay.Results: The results of the preparation maintain the curved canal shape.Conclusions: Preparation of curved canal using a single file reciprocating system can maintain the original canal shape and bring out good result.